Analisis Kualitas Pelayanan dan Kualitas Produk Toko Ud. Ulfa Husna Jaya Terhadap Kepuasan Pelanggan Pada Transaksi Jual Beli Peralatan Bangunan Di Desa Dah Aceh - Rediansyah Saranan; Zainarti Zainarti (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2023)
This study aims to analyze service quality and product quality at UD stores. Ulfa Husna Jaya on customer satisfaction in buying and selling transactions for building and agricultural equipment in Dah Village, Rundeng District, Subulussalam City, Aceh. This research is a quantitative research, namely research using data in the process of completion, the characteristics of this research are researchers functioning as the main instrument in data collection. This study uses methods such as data analysis, interviews, and observation. The results of the data will be explained based on the findings in the field. And the method in this study uses a quantitative descriptive method, namely the author conveys facts and phenomena by describing the results obtained in the field. The results of the t test (Partial Test) show that service quality has a partial and significant effect on customer satisfaction in buying and selling transactions of building and agricultural equipment. Then, based on the test results, it shows that service quality and product quality have a simultaneous or joint and significant effect on customer satisfaction in the buying and selling of building and agricultural equipment.